THE WEIGHT OF TOXIC LEADERSHIP: A QUALITATIVE EXPLORATION OF EMPLOYEE EXPERIENCES UNDER TOXIC LEADERSHIP - Abhishek Shukla, (PEOPLE: International Journal of Social Sciences, 2026)
Toxic leadership, which is characterized by abusive, manipulative, and destructive behaviour on the part of organizational leaders, poses significant obstacles to the well-being of employees, the organization's culture, and its overall performance. While toxic leadership persists and has detrimental effects, it is a complex and multifaceted phenomenon that requires an in-depth investigation. From the perspective of employees, this qualitative study aims to provide a detailed investigation of the profound effects that toxic leadership has on employee well-being and behaviour. In this research, in-depth interviews and thematic analysis will be used to examine the experiences and responses of employees who have experienced toxic leadership. The toxic leadership in an organization has emerged as a major concern in organizational behaviour research, having a profound impact on the well-being of employees and the health of organizations. The findings of this study are expected to identify and analyse how employees cope with these adverse impacts as well as offer interventions that organizations can implement to mitigate the adverse effects of toxic leadership. It is also anticipated that the findings from this study will contribute to future research on toxic leadership and the long-term effects it may have on the well-being of an organization.